Assessment of Serum Levels of Oxidative Stress Markers and Heat Shock Proteins in Myocardial Infraction Patients - Sidra Anwar, Awais Ur Rehman, Asma Hussain, Abdul Rahman Abid, Sobia Saeed, Hafiza Sobia Ramzan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Heat stress proteins also known as shock proteins are the molecular chaperones due to various stimuli response to heat and ischemic injury to the cells. They are important in folding and degradation of other proteins involved in genesis of cardiovascular pathologies. Objectives: The main aim is to upgrade the role of oxidative markers and these stress proteins not only in development but also in evolution related to heart disease. Material and methods: Subjects were selected as diagnosed myocardial infarction in Faisalabad institute of cardiology, Faisalabad Division, Punjab. All subjects were further categorized as risk group and non-risk group on the basis of their risk factors history using ACC/AHC 2017 guided criteria for detection of myocardial infarction included chest pain, ECG finding and cardiac enzymes. Results: Data clearly depicts the demographical and hematological profile i-e complete blood picture of patients with diagnosed myocardial infraction and control subject. Hemoglobin as a highly advanced allosteric protein present in the form of HbA with two α and two β chains while globin chains are synthesized in erythrocytes cytosol. Conclusion: Despite of increasing evidence from the recent data, it is recommended that functions of these heat shock proteins related to guard cells against programmed apoptosis from stressful aspects e.g. infection, mechanical stress, oxidized low density lipoprotein and oxidants are also known as stress proteins. Keywords: Stress Proteins, Atherosclerosis, Apoptosis, Myocardial Infarction, Oxidative Markers